THE INFLUENCE OF LEADERSHIP STYLE AND SERVICE QUALITY ON PUBLIC SATISFACTION IN KELURAHAN PONDOK JAGUNG, SERPONG UTARA, TANGERANG SELATAN - Bahrudin, Ahmad (BAIK Publishers, 2025)
This study aims to determine the effect of leadership style and service quality on public satisfaction in Pondok Jagung Village. This research is motivated by the importance of leadership and quality public services in creating public satisfaction as indicators of successful governance at the village level. The method used was a quantitative survey approach. The sample in this study consisted of residents who received direct services from the village, selected purposively. Data collection was conducted through a closed-ended questionnaire with a Likert scale, which was then analyzed using multiple linear regression. The analysis results indicate that leadership style has a positive and significant effect on public satisfaction, contributing 31.4%. Service quality also has a positive and significant effect on public satisfaction, contributing 30.6%. Simultaneously, leadership style and service quality significantly influence public satisfaction, with a coefficient of determination (R²) of 42.2%, meaning that the two independent variables explain 42.2% of the variation in public satisfaction. These findings emphasize the importance of improving leadership style and enhancing the quality of public services in building public trust and satisfaction